Android-Based Physics Learning Media with 5E Model Using Smart Apps Creator on Light Waves for Grade 11 - Dalimunte, Firda Clatika Sari; Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi (Universitas Ahmad Dahlan, 2025)
Physics is a subject that contains several abstract concepts, one of which is the topic of light waves. This topic can be better understood through learning media to help students grasp the material more effectively. This study aims to determine the effectiveness of Android-based mobile learning in physics, integrated with the 5E Learning Cycle model, as a support tool for teaching light wave material in senior high school. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were analyzed using descriptive statistics by calculating the percentage scores from expert validation, student responses, and evaluation tests. The results showed an average score of 73.95% from media experts, 89.65% from content experts, and 69.44% from language experts. The overall expert validation average was 77.68%, indicating that the media is suitable and usable in schools. Additionally, the average score from student response tests was 92.71%, reflecting a very positive reaction from students. Thus, this mobile learning media is adequate for teaching light waves to 11th-grade high school students. The findings imply that integrating pedagogically grounded digital tools into science education may enhance conceptual understanding, promote independent learning, and offer scalable alternatives for remote and blended learning scenarios.